Pelatihan Seni Kaligrafi Islam dalam Peningkatan Kreativitas Siswa di SMP Negeri 2 Wiradesa Kabupaten Pekalongan - Fatmawati Nur Hasanah; Rofiqotul Aini; Toni Setiawan; Bayu Irawan; Moh. Nurul Huda (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Islamic calligraphy is one of the cultural treasures of the Indonesian archipelago which must be preserved. Learning Islamic calligraphy increases the imagination, creativity and intellectual development of students. Of course, there are not many state school students who are talented in the art of calligraphy compared to private Islamic schools. But this does not mean that they do not have creativity in Islamic calligraphy. This community service activity aims to overcome this. Islamic calligraphy training activities use the Participatory Action Research (PAR) approach where the cycle includes KUPAR (to Know, to Understand, to Plan, to Action and to Reflection). This service activity was carried out for students at Wiradesa Public Middle School 2, Pekalongan Regency, for 2 weeks. The result of this community service activity in the form of training in the art of Islamic calligraphy is that Wiradesa 2 Public Middle School students are very enthusiastic in learning to write Islamic calligraphy. This is evidenced by the results of Islamic calligraphy that has been made by students of Wiradesa 2 Public Middle School, their writing is increasingly developing and according to the rules of Islamic calligraphy. With this training, students become confident to develop their creativity and express their imagination in the form of works in the form of Islamic calligraphy.